gMendel® Test-SCAN, a novel Decision-Supporting tool for Mass Screening of Aneuploidies, based on Oxford Nanopore technology - Schack, Anne Kristine; Garrido Navas, Carmen; Galevski, David; Nikov, Aleksandar; Madjarov, Gjorgji; Kyriakidis, Chris; Velkoski, Zoran; Krych, Lukasz (SPRINGERNATURE, 2024)
SEQUENCING TECHNOLOGY has revolutionized over the last decade. Though karyotyping and aneuploidy detection is still carried out with the conventional method, fluorescence in situ hybridization (FISH) [1]. Illumina, a next-generation sequencing technology, has shown to be efficient as a detection method [2]. Despite both FISH and NGS are efficient for detection and karyotyping, they lack the combination of being time-, and cost-efficient [3]. THE gMendel® Test-SCAN demonstrates a cost-effective, end-to-end assay with diagnostic utility for postnatal detection of aneuploidies based on Oxford Nanopore Technologies (ONT) in the combination of Artificial Intelligence. With gMendel® Test-SCAN hundreds of samples can be analyzed simultaneously on a single MinION/GridION Flow Cell in less than 24h with high specificity and sensitivity. Our data analysis platform, Phivea®, is fully automated and perform in real-time using cutting-edge machine learning approaches.